The apparitional lesbian: Female homosexuality and modern culture - Castle, Terry (Columbia University Press, 1995)
In essays on literary images of lesbianism from Defoe and Diderot to Virginia Woolf and Djuna Barnes, on the homosexual reputation of Marie Antoinette, on the lesbian writings of Anne Lister, Sylvia Townsend Warner, and Janet Flanner, and on Henry James's The Bostonians, Castle shows how a lesbian presence can be identified in the literature, history, and culture of the past three centuries.
Keywords: approches et analyses; arts; discipline; identités LGBTQIA2+; lesbianisme; études littéraires